Pengaruh Varietas dan Media Tanam pada Sistem Hidroponik Tetes Tomat Ceri di Dataran Rendah - Nur Kholida Lisa Wulansari; Ratna Dwi Hirma Windriyati; Ari Kurniawati (Agro Bali : Agricultural Journal, 2022)
The study aims at getting the right media and the appropriate varieties for cherry tomato production using hydroponic drops in lowland areas, doing a vecial experiment with 2 factors: planting media and variety. The plant medium is cocopeat, chaff and ferns. The varieties used were Red Ruby, Rojita, and Juliet. The environmental design used is the random design of the group of 3 variable reenactments observed being the height of the plants, the diameter of the bar, the volume of the root, the weight of the fresh root, the weight of the fresh header, the weight of fresh brash and the bushy weight of the data plant that is obtained is analyzed using a variegated analysis at 5% error. If different is real then the analysis is carried out using the smallest real difference analysis at the point of error 5% to find out the difference between treatments. The conclusion of the study is 1) the production of cherry tomatoes in the lowlands USES the hydroponic system of drops affected only by varieties and 2) the Rojita is the best variety for harvesting cherry tomatoes using drip hydroponics compared with red ruby and Juliet.